A comparative exergoeconomic analysis of different ORC configurations for binary geothermal power plants. (15th November 2015) - Zare, V.
Highlights: Three ORC configurations for geothermal power plants are compared exergoeconomically. ORC with internal heat exchanger has the best thermodynamic performance. Simple ORC has the best economic performance. Abstract: The main goal of this research is to investigate and compare the performance of three configurations of organic Rankine cycle (ORC) for binary geothermal power plants from the viewpoints of both thermodynamics and economics. The considered configurations are: Simple organic Rankine cycle (S-ORC), Regenerative organic Rankine cycle (R-ORC) and organic Rankine cycle with Internal Heat Exchanger (ORC-IHE). To assess the cycles' performances, thermodynamic and exergoeconomic models are developed and a parametric study is carried out prior to the optimization with respect to the total product cost minimization, as the objective function. Also, a profitability evaluation of the investigated systems is performed based on the total capital investment and payback period. The results indicate that, from the thermodynamic point of view (first and second law efficiencies), the ORC-IHE has superior performance while from the economic viewpoint the S-ORC is the best case among the considered cycles.